Determination of Ghost Fishing Starting Time by Four Different Baited Fish Traps in the Çanakkale Strait (North Aegean Sea) - Talip İbin; Adnan Ayaz (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2021)
In this study, the starting time of ghost fishing in baited fish traps were determined. Two separate trials using 4 different types of fish traps (foldable, conical, “O” shaped Round and cylindrical) were carried out in the Çanakkale Strait at a depth of 5m between July - December 2013. A total of 12 fish traps (3 for each trap type) were used in the study. Each trial lasted a period of 45 days. Major features of the traps were as follows: the foldable fish trap had “V” shaped inclined funnel; the conical fish trap had a conical entrance from the top; The “O” shaped fish trap had a “V” shaped entrance on the base; the cylindrical trap had a conical entrance on the side. In all trials fresh sardine, black mussel and bread placed in a net bag were used as bait and fixed in the traps. Underwater observations showed that fish entrapped in all trap types escaped from the traps within 8-10 days. Fish mortality was due to accidental entanglement of fish on the mesh material covering the traps or due to predation. Molluscs such as octopuses and squids escaped within 4-7 days whereas crabs suffered from cannibalism or starvation due to their lower escape rates. In conclusion, in the present study while trap ghost fishing for fish and cephalopods were not observed, ghost fishing for crabs were observed and was a factor of entrance design and location on traps.